Orcs Lives Matter: Representation of African Americans in Bright Film - Shafira Ayuningtyas; Pita Merdeka (Insaniyat : Journal of Islam and Humanities, 2021)
Exploring the way Orcs are portrayed in the Bright film are the focus of this research and futher analyzing the ideology within. This research uses the qualitative research method to help answering the research questions on how Orcs are represented in Bright and how representations reflect the ideology of the text. Additionally, Hall’s representation and ideology theories are applied in the process to provide an insight into the research problems. The research found that Orcs in Bright are constructed in a very like ways as African Americans as they are portrayed as the designated bad guys, targets for animalization and victims of police brutality which match the image of African Americans in American society. These portrayals of Orcs leads to the discussion of Orcs’ poor social standing in society in comparison to other races in the film and in result reflects the ideology the text tries to convey that is black inferiority, as shown by the way the American system and society treated them. Overall, this research can be used as a reference for researches on representation of African Americans and racial allegories in literature.